The spy in the museum : how Rose Valland saved art from the Nazis - McGuire, Erin (Beach Lane Books, an imprint of Simon & Schuster Children's Publishing Division, 2025)
"This biography tells the true story of Rose Valland's valiant efforts to save thousands of works of art during World War II by doing the only thing she could: Becoming a spy in her own museum"--